The dithiol mechanism of class I glutaredoxins promotes specificity for glutathione as a reducing agent - Lukas Lang; Philipp Reinert; Cedric Diaz; Marcel Deponte (Redox Biology)
Class I glutaredoxins reversibly reduce glutathione- and nonglutathione disulfides with the help of reduced glutathione (GSH) using either a monothiol mechanism or a dithiol mechanism. The monothiol mechanism exclusively involves a single glutathionylated active-site cysteinyl residue, whereas the dithiol mechanism requires the additional formation of an intramolecular disulfide bond between the active-site cysteinyl residue and a resolving cysteinyl residue. While the oxidation of glutaredoxins by glutathione disulfide substrates has been extensively characterized, the enzyme-substrate interactions for the reduction of S-glutathionylated glutaredoxins or intramolecular glutaredoxin disulfides are still poorly characterized. Here we compared the thiol-specificity for the reduction of S-glutathionylated glutaredoxins and the intramolecular glutaredoxin disulfide. We show that S-glutathionylated glutaredoxins rapidly react with a plethora of thiols and that the 2nd glutathione-interaction site of class I glutaredoxins lacks specificity for GSH as a reducing agent. In contrast, the slower reduction of the partially strained intramolecular glutaredoxin disulfide involves specific interactions with both carboxylate groups of GSH at the 1st glutathione-interaction site. Thus, the dithiol mechanism of class I glutaredoxins promotes specificity for GSH as a reducing agent, which might explain the prevalence of dithiol glutaredoxins in pro- and eukaryotes.